Initial Deformation of the Northern Tibetan Plateau: Insights From Deposition of the Lulehe Formation in the Qaidam Basin. Issue 2 (27th February 2019) - Cheng, Feng; Garzione, Carmala N.; Jolivet, Marc; Guo, Zhaojie; Zhang, Daowei; Zhang, Changhao; Zhang, Qiquan
Abstract: The Paleogene Lulehe Formation marks the onset of deposition in the Qaidam basin and preserves evidence of the initial topographic growth of northern Tibet. However, limited outcrops impede understanding of the sedimentary features of the Lulehe Formation as well as the tectonic relationship between the basin and surrounding topography. To fill this gap, we investigated core samples along the basin margin and conducted flexural modeling to estimate the topographic load of the Qilian Shan and Eastern Kunlun Shan during the deposition of the Lulehe Formation. Core samples reveal that the Lulehe Formation mainly consists of distal fluvial to marginal lacustrine deposits and proximal fluvial deposits along the southern margin of the basin while characterized by proximal alluvial fan deposits along the northern margin of the basin. Together with evidence for faulting shown on the seismic profiles, we infer that simultaneous deformation within the Qilian Shan and Altyn Tagh Shan during the Paleogene resulted in accumulation of coarse detrital deposits in the northwestern and northeastern Qaidam basin. The simultaneous deformation within the Altyn Tagh Shan and Qilian Shan since the Paleogene supports the idea that deformation in these two regions is kinematically linked. One‐ and two‐load beam flexural modeling indicates that the topographic load generated by both the Eastern Kunlun Shan and the Qilian Shan is responsible for the subsidence of the Qaidam basin during deposition of the Lulehe Formation. Our results highlight the initial relative high topography in the northern Tibetan plateau during the early Cenozoic. Key Points: We carry out flexural modeling to estimate the initial topographic load of the Qilian Shan and Eastern Kunlun Shan Lulehe Formation consists of distal fluvial‐marginal lacustrine and proximal fluvial‐alluvial fan deposits along the margins of the basin Both Qilian Shan and Eastern Kunlun Shan topographic loads account for the initial subsidence of the Qaidam basin